Analisis Kesalahan Siswa Dalam Menyelesaikan Operasi Perkalian Matriks Kelas XI IPS 2 SMA Negeri 2 Gunung Talang - Fahmi Aulia Zikra; Melisa Melisa; Hafizah Delyana (STKIP PGRI Sumatera Barat, 2023)
This research is motivated by the many mistakes made by students in working on questions on matrix material. The aim of the study was to find out how the description of the mistakes made by students of class XI IPS 2 SMA Negeri 2 Gunung Talang. The research method used is descriptive with a quantitative approach. The subjects of this study were students of class XI IPS 2 SMA Negeri 2 Gunung Talang. The sampling technique used purposive sampling technique. Research instruments were used to collect data in the form of tests, interviews and documentation. The test results were analyzed according to Newman's error criteria The results showed that in the indicator of scalar multiplication with matrix, the errors found in (1) subjects with high ability were transformation errors, writing the final answers, (2) subjects with moderate abilities were errors in process skills and errors in writing the final answers, and ( 3) subjects with low ability are understanding errors, transformation errors and errors in writing the final answer. Whereas in the matrix multiplication indicator, the errors found in (1) subjects with high ability were transformation errors, errors in writing the final answer, (2) subjects with medium ability were reading errors, comprehension errors, transformation errors, process skill errors and final answer writing errors, and (3) subjects with low ability are reading errors, understanding errors, transformation errors, and final answer writing errors